Causality Relationship between Electricity Consumption and Economic Growth in Indonesia and Thailand - Bunnag, Tanattrin (International Journal of Energy Economics and Policy, 2020)
This paper examined the existence and direction of the causal relationship per capita electricity power consumption and per capita economic growth in Indonesia and Thailand. The results of analysis were used to suggest policymakers regarding formulation of electricity in Indonesia and Thailand. The data used in this study was the yearly data from 1971 to 2014. The Cointegration and Granger Causality approaches were employed. The empirical results overall showed that had established a long run correlation among consumption of electric power and economic growth. Moreover, the Granger Causality approach had recognized a one-way of casual direction flowing from electric power consumption to economic growth in Indonesia. Thailand, empirical results had no long run correlation among consumption of electric power and economic growth. The Granger Causality approach had recognized no way of casual direction flowing from electric power consumption to economic growth. Finally, these results implied that, in the context of Indonesia, policy maker should focus on electric power consumption and surplus electricity supply policies rather than focus on initiate electricity conservation. For Thailand, policymakers should focus on initiate electricity conversation policies rather than focus on surplus electricity supply. Keywords: electric power consumption, economic growth, the causal relationship JEL Classifications: C13, C20 DOI: https://doi.org/10.32479/ijeep.10159